Aromatic effector activation of the NtrC-like transcriptional regulator PhhR limits the catabolic potential of the (methyl)phenol degradative pathway it controls. - Ng, L C (1995)
Pseudomonas putida P35X (NCIB 9869) metabolizes phenol and monomethylphenols via a chromosomally encoded meta-cleavage pathway. We have recently described a 13.4-kb fragment of the chromosome that codes for the first eight genes of the catabolic pathway and a divergently transcribed positive regulator, phhR. The eight structural genes lie in an operon, the phh operon, downstream of a -24 TGGC, -12 TTGC promoter sequence. Promoters of this class are recognized by RNA polymerase that utilizes the alternative sigma 54 factor encoded by rpoN (ntrA) and are positively regulated by activators of the NtrC family. In this study, we have identified the coding region for the 63-kDa PhhR gene product by nucleotide sequencing of a 2,040-bp region and polypeptide analysis. PhhR was found to have homology with the NtrC family of transcriptional activators, in particular with DmpR, the pVI150-encoded regulator of (methyl)phenol catabolism by Pseudomonas sp. strain CF600. By using a luciferase reporter system, PhhR alone was shown to be sufficient to activate transcription from the phh operon promoter in an RpoN+ background but not an RpoN- background. Luciferase reporter systems were also used to directly compare the aromatic effector profiles of PhhR and DmpR. Evidence that the difference in the growth substrate ranges of strains P35X and CF600 is due to the effector activation specificities of the regulators of these systems rather than the substrate specificities of the catabolic enzymes is presented.